PROTECTION OF FARMER'S RIGHTS UNDER THE PLANT VARIETIES PROTECTION REGIME: NATIONAL AND INTERNATIONAL PERSPECTIVES (NATIONAL CAPITAL LAW JOURNAL, 2004)
NA
Keywords: Farmer’s Rights; Plant Variety Protection; Intellectual Property Rights; UPOV Convention; Plant Breeders’ Rights; Benefit Sharing; Traditional Knowledge; Biological Diversity